Influence of age and gender on gait kinematics of pelvis and hip in healthy adults aged 19–60 years - Mullerpatan, Rajani; Shetty, Triveni; Agarwal, Bela (Frontiers in Bioengineering and Biotechnology, 2025)
PurposePelvic and hip motion are pivotal in maintaining postural control and energy efficient gait. An insight into influence of age and gender on the coupled motion of hip and pelvis in gait-cycle will guide clinical rehabilitation strategies and pertinent technology-design for specific age-groups. Therefore, present study evaluated pelvic and hip-joint gait kinematics in healthy females and males across adult-hood.MethodsFollowing signed-informed consent, pelvic and hip kinematics in 3-planes during stance-phase of gait were measured using 12-camera motion system and 2 force-plates, in 200 healthy Indian female and male volunteers (19–60years) stratified into 4-groups (19–30 years; 31–40 years; 41–50years; 51–60 years).ResultsWith advancing age, males and females demonstrated a gradual rise in hip adduction (p < 0.01) in coronal plane. Sagittal plane pelvic and hip kinematics did not change with advancing age among males whereas females above 30 years Demonstrated greater pelvic drop (49%), pelvic tilt (35%) and hip adduction (69%) compared to females below 30 years (p < 0.01). In comparison to males, females demonstrated greater peak anterior pelvic tilt (32%), greater pelvic hike (28%) and protraction (28%) in 50–60 years age-group (p < 0.05). Females across all age-groups demonstrated greater hip adduction compared to males (p < 0.05).ConclusionPresent findings add age and gender characterized gait-kinematics data of healthy adults from the most populous country to the existing 3-D data of gait from different populations. Clinicians and engineers, can leverage this knowledge of changing gait kinematics of healthy adults to design specific therapeutic strategies for aging men and women to optimize gait kinematics and advance design and development of locomotor technology suitable for people with rehabilitation needs across the globe.